Assessing the Relationship Between Liver and Spleen Volumes in Patients with Liver Cirrhosis Using the Cavalieri Principle on Cross-Sectional Images - Özgen, M.N.; Sahin, A.; Çelikyay, R.; Sahin, B. (Ondokuz Mayıs Üniversitesi, 2024)
In the early stages of liver cirrhosis, hepatomegaly is observed, while in the later stages, enlargement of the spleen is observed due to shrinkage of the liver and increased pressure in the portal circulation. This study examined liver and spleen volumes and their proportional relationship in healthy controls (HC) and patients with liver cirrhosis (LC) using computed tomography (CT) images. CT images from 52 LC patients (26 females, 26 males) and 52 HC individuals (26 females, 26 males) aged 18 to 85 years were analyzed. Liver and spleen volumes, as well as spleen/liver+spleen volume ratio were calculated using the Cavalieri principle. Volume and ratio data were compared between the HC and LC groups. In addition, volumes and ratios were analyzed according to the disease classes in patients. Liver volume was greater in LC patients (1488.9 ± 502.3 cm3) than in HC individuals (1321.8 ± 277.1 cm3) (p = 0.038). Spleen volume was significantly greater in LC patients (676.8 ± 347.02 cm3) than in HC individuals (249.37 ± 101.16 cm3) (p < 0.001). The spleen/liver+spleen volume ratio was significantly higher in LC patients (30.75 ± 12.22%) than in HC individuals (15.68 ± 5.09%) (p < 0.001). No significant difference in volume ratios was observed between LC and HC groups based on sex (p > 0.05). Liver volumes were 1670.7 cm3, 1357.4 cm3, and 1087.3 cm3, while the spleen/liver+spleen volume ratios were 26.71%, 33.49%, and 40.26% in LC classes A, B, and C respectively. As the cirrhosis class progressed, liver volume decreased (p = 0.010), and the spleen/liver+spleen volume ratio increased (p = 0.020). Liver and spleen sizes, as well as the spleen/liver+spleen volume ratio did not vary by sex. These values can serve as baseline parameters independent of sex. Liver and spleen volumes, as well as their ratios, were greater in LC patients than in HC individuals. As the class of cirrhosis progressed, liver volume decreased, and the ratio increased. Our findings suggest that the spleen/liver+spleen volume ratio can be used to evaluate the classes of liver cirrhosis. © 2024 Ondokuz Mayis Universitesi. All rights reserved.
Keywords: Cavalieri Principle; Cirrhosis; Computed Tomography; Liver; Spleen; Volume